SharePoint 2016 user's guide learning Microsoft's business collaboration platform - Smith, Tony (2016)
Learn how to make the most of SharePoint 2016 and its wide range of capabilities to support your information management, collaboration, and business process management needs. Whether you are using SharePoint as an intranet or business solution platform, you will learn how to use the resources (such as lists, libraries, and sites) and services (such as search, workflow, and social) that make up these environments. In the fifth edition of this bestselling book, author Tony Smith walks you through the components and capabilities that make up a SharePoint 2016 environment. He provides step-by-step instructions for using and managing these elements, as well as recommendations for how to get the best out of them. How to create and use common SharePoint resources like lists, libraries, sites, pages and web parts Understand when and how workflows and information management policies can be used to automate process Learn how to take advantage of records retention, management, and disposition Making the most out of SharePoint search services How to take advantage of social capabilities to create social solutions.
Viewing Items in the Recycle Bin. - Includes bibliographical references. - Print version record
Keywords: Microsoft SharePoint (Electronic resource); COMPUTERS; Networking; Intranets & Extranets; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference; Microsoft